FISHERS’ PARTICIPATION IN POVERTY ALLEVIATION PROGRAMME : A CASE STUDY IN TWO LESS-DEVELOPED VILLAGES IN PEMALANG DISTRICT, CENTRAL JAVA - Waridin . (JOURNAL OF COASTAL DEVELOPMENT, 1999)
This study was aimed to assess the level of fishers’ participation alleviation programme in two less-development villages at the coastal area in Pemalang District, Central Java. The study found that to a certain extent, the poor fishers have participated in the four phases of the programme accomplishment: in decision-making, implementation, sharing benefits, and evaluation. However, the intensity of participation in each phase was low. Several effort to improve fishers’ participation in the programme such as providing appropriate technical and management advisory support and sufficient information to the target members were recommended.